Kualitas Dadih Kacang Tunggak (Vigna Unguiculata Dengan Penambahan Jenis Susu dan Perasa Alami Melalui Pemeraman yang Berbeda - Sholekah, Dantik, Dra. Aminah Asngad, M.Si (2017)
Curd is one of the traditional milk fermentation products that is very typical in West Sumatra. The curd is made with the basic ingredients of buffalo milk that is put in bamboo and covered with banana leaves, then fermented for 48 hours. The aim of the study was to know quality cowpea curd with the addition of milk type and natural flavor through different curing. The method of this research was Complete Randomized Design (CRD) with 2 factors, namely: Milk type: control (J0), cow milk (J1), Etawa milk (J2), and curing time: 42 hours (L1), 48 hours (L2 ), 54 hours (L3). The results showed the highest carbohydrate content at treatment J1L2 that is 63,82 g / l, the lowest carbohydrate level at treatment J0L3 that is 34,99 g / l. Curd products have a creamy, yellowish, and yellow color, distinctive aroma of the type of milk used, the taste of acid, the texture is soft enough, the acceptance of panelists on all treatments a little like. There is an influence of the addition of milk type and length of curing to carbohydrate content of curd.